Determining Entrepreneurial Intention in Students: The Role of Risk-Taking Propensity, Family Support, Self-Efficacy and Entrepreneurship Education - Salendu, Putri Christy M; Ayu Salsabila, Annisa; Ramadhan Akbar, Fathur; Adhilia, Firas; Ardi, Muhammad (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The low interest in entrepreneurship among university students is a serious problem, despite the widespread implementation of entrepreneurship education in universities. Internal factors such as risk-taking propensity and self-efficacy, as well as external factors such as family support, have not yet played an optimal role in increasing entrepreneurial intentions. This study aims to analyze the influence of risk-taking propensity, family support, self-efficacy, and entrepreneurship education on students' entrepreneurial intention. The research method used was quantitative with a cross-sectional approach through the distribution of questionnaires to final-year students and analyzed using SmartPLS. The results showed that self-efficacy had a significant effect on entrepreneurial intentions, while risk-taking tendencies, family support, and entrepreneurship education did not. The implications of this study emphasize the importance of strengthening internal factors and entrepreneurship curriculum to foster the entrepreneurial spirit of the young generation in Indonesia.Rendahnya minat berwirausaha di kalangan mahasiswa menjadi permasalahan serius meskipun Pendidikan kewirausahaan telah banyak diimplementasikan di perguruan tinggi dan telah dilakukan secara masif. Faktor internal seperti keberanian mengambil resiko dan efikasi diri, serta faktor eksternal seperti dukungan keluarga belum sepenuhnya berperan optimal dalam meningkatkan intensi berwirausaha. Penelitian ini bertujuan untuk menganalisis pengaruh risk-taking propensity, family support, self-efficacy, dan entrepreneurship education terhadap entrepreneurial intention mahasiswa. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan cross-sectional melalui penyebaran kuesioner terhadap mahasiswa tingkat akhir dan di analisis menggunakan SmartPLS. Hasil penelitian menunjukan bahwa self-efficacy berpengaruh signifikan terhadap entrepreneurial intention, sedangkan risk-taking propensity, family support, dan entrepreneurship education tidak berpengaruh signifikan. Implikasi penelitian ini menegaskan pentingnya penguatan faktor internal dan kurikulum kewirausahaan untuk menumbuhkan jiwa wirausaha generasi muda di Indonesia.